An Assessment of the Level of Development of the Social Infrastructure of Regions in the Russian North and Arctic - Toropushina, E.E. (Problems of economic transition, 2018)
This article presents the author's method for assessing the level of development of the social infrastructure of the Russian North and Arctic. It develops corrective coefficients for the accessibility of medical care and education and makes conclusions about the necessity to use these coefficients when making decisions about the development of the social infrastructure. In addition, it determines that the real level of health care services provided to the population remains low in all regions of the Russian Federation's North and Arctic.